Cu, Zn Dopants Boost Electron Transfer of Carbon Dots for Antioxidation. Issue 31 (1st July 2021) - Xue, Sheng; Zhang, Tingwei; Wang, Xiaokai; Zhang, Qinhua; Huang, Siyang; Zhang, Liwei; Zhang, Liyu; Zhu, Wenjie; Wang, Yin; Wu, Mingbo; Zhao, Qingshan; Li, Peifeng; et al.
Abstract: Enzyme‐mimicking nanomaterials for antioxidative therapy is a promising star to treat more than 200 diseases or control their progressions through scavenging excessive reactive oxygen species (ROS), such as O2 − and H2 O2 . However, they can inversely produce stronger ROS (e.g., OH) under many disease conditions (e.g., low pH for myocardial ischemia). Herein, a biocompatible ‐Cu‐O‐Zn‐ bimetallic covalent doped carbon dots (CuZn‐CDs) processing both catalase (CAT) and superoxide dismutase activities are reported, mainly because of their abundant electrons and the excellent electron transfer abilities. In addition, Cu dopant helps to balance the positive charge at Zn dopant resulting from low pH, enabling CuZn‐CDs to still process CAT ability rather than peroxidase ability. Benefiting from it, CuZn‐CDs exhibit sufficient in vitro ROS scavenging ability and cardiomyocyte protective effect against ROS‐induced damage. In vivo results further demonstrate that CuZn‐CDs can protect the heart from ischemia‐reperfusion injury. In addition to antioxidative therapy, the rapid renal clearance and low toxicity properties of CuZn‐CDs in animal model reveal high biocompatibility which will facilitate clinical use. Abstract : The ‐Cu‐O‐Zn‐ bimetallic doping carbon dots process great both catalase and superoxide dismutase activities even under high temperature, alkaline and acidic conditions, exhibiting sufficient in vitro reactive oxygen species scavenging ability and cardiomyocyte protective effect. This bimetallic system synergistically boosts the electron transfer ability and balances the positive charge, thus ensuring excellent antioxidation activity.